(untitled) (Journal of Mathematics Mechanics and Computer Science, 2024)
The research work is devoted to the kinetics of adsorption. Needless to say that physical adsorption is of great interest in heat industry according to the number of research papers published in the area annually. The working pair of carbon dioxide and consolidated tablet of AC was considered. The mathematical model built for a cylindrical coordinate system, so the computational domain is a rectangle corresponding to the radial section of the tablet. The rate of adsorption implemented using the LDF (linear driving force) model. The temperature map was constructed for analyzing the behavior of the temperature field. Curves of instantaneous uptake and simulated average temperature are obtained. Simulation results are compared with experimental data and shows good agreement. The study also presents findings of a grid sensitivity analysis. The developed solver is the subject to further expansion to consider more quantities, such as change in porosity, volatile gas concentration, etc.